Planktonic foraminiferal assemblages reflect warming during two recent mid-latitude marine heatwaves - Lane, M. Kelsey; Fehrenbacher, Jennifer S.; Fisher, Jennifer L.; Fewings, Melanie R.; Crump, Byron C.; Risien, Craig M.; Meyer, Grace M. L.; Schell, Faith (Frontiers in Marine Science, 2023)
Under future climate scenarios, ocean temperatures that are presently extreme and qualify as marine heatwaves (MHW) are forecasted to increase in frequency and intensity, but little is known about the impact of these events on one of the most common marine calcifiers, planktonic foraminifera. Planktonic foraminifera are globally ubiquitous, shelled marine protists. Their abundances and geochemistry vary with ocean conditions, and fossil specimens are commonly used to reconstruct ancient ocean conditions. Planktonic foraminiferal assemblages are known to differ globally with sea surface temperature, primary productivity, and other hydrographic conditions, but have not been studied in the context of mid-latitude MHWs. For this study, the community composition and abundance of planktonic foraminifera were quantified for 2010-2019 along the Newport Hydrographic Line, a long-term monitoring transect at 44.6°N in the Northern California Current (NCC). Samples were obtained from archived plankton tows spanning 46 to 370 km offshore during annual autumn (August – October) cruises. Two MHWs impacted the region during this timeframe: the first during 2014-2016 and a second, shorter duration MHW in 2019. During the 2014-2016 MHW, warm water subtropical and tropical foraminifera species were more prevalent than the typical polar, subpolar, and transitional species common to this region. Cold water species were abundant again after the first MHW dissipated in late 2016. During the second, shorter-duration MHW in 2019, the assemblage consisted of a warm water assemblage but did not include tropical species. The foraminiferal assemblage variability correlated with changes in temperature and salinity in the upper 100 meters and was not correlated with distance offshore or upwelling intensity. These results suggest that fossil foraminiferal assemblages from deep sea sediment cores may provide insight into the magnitude and frequency of past MHWs.